Physiological variables associated with performance in a European professional male rugby team: Analysis of a training intervention - Guerrero, S.; Pardo, P.; Solà, J.; Piedra, A.; Albesa-Albiol, L.; Sanchez, J. A.; Peña, J.; Daza, G.; Solé, J.; Caparrós, T. (Apunts Sports Medicine, 2024)
The main objective of this study was to identify the impact on conditional variables through a training intervention. A retrospective observational study was conducted in a professional rugby team, where an intervention was conducted for 4 weeks. Data were collected for a total of 18 weeks: 14 weeks pre-intervention, including 7 matches; and 4 weeks post-intervention, including 4 matches. The variables selected and analysed were distance (m), sprint distance (m), distance per minute (m/min), maximum speed (km/h), high intensity actions (n) and accelerations and decelerations >3m/s² (n). In training, a significant difference was found before and after the intervention in Dist. Sprint (t=4.303), in Vel. Max (t=4.141), and in Acc+Dec>3m/s² (t=2.939). In the match data, changes were observed in the mean of the variables before and after the intervention, highlighting the Dist. Sprint (t=-2.295) and Max Speed (t=-0.805). In this specific context, coaches and professionals should be aware of the conditional variables that have the greatest impact on the game, with the aim of optimising the training methodology and focusing on the specific needs of each team to improve performance.